PULMONARY ASPIRATION DURING PROCEDURAL SEDATION : A SYSTEMATIC REVIEW - Nurochman Sidik, Fajar; Muhammad Suharyo, Dhimas; Solehudin, Hipni; Lesmana Putri, Fitria (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Aspiration of the pulmonary during sedation procedural of anesthesia has received considerable research attention, little is known about the aspiration of pulmonary during operational general anesthesia.Aims : This systematic review is to review the association of sedation anesthesia and its effects on pulmonary aspiration.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 418 articles, whereas the results of our search on SCIENCE DIRECT brought up 372 articles. The results of the search conducted for the last year of 2014 yielded a total 16 articles for PubMed and 32 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria.Conclusion: In summary, pulmonary aspiration complicating non-endoscopic procedure sedation was found in this systematic review with complete recovery as the usual outcome. Aspiration of pulmonary occurred not in any of the individuals. Aspiration under anesthesia with sedation appears to be uncommon, unique and generally benign, however careful vigilance is still advised.